Mechanisms of Oncogenesis An update on Tumorigenesis - Coppola, Domenico (Cancer Growth and Progression ;, 2010)
This volume is part of a book series that was first published in 10-volumes by Kluwer in 1989 under the series editorship of Professor Hans E. Kaiser, D.Sc., former Professor of Pathology at the School of Medicine, University of Maryland at Baltimore, MD, USA along with other leaders in the field of Cancer. In order to encompass the growing body of knowledge on various aspects of cancer growth and progression since then, the series has now been expanded to 17 volumes. This volume is a comprehensive update on the mechanisms of tumorigenesis, and includes the advances in the field, as provided by the use of the most recent molecular techniques (microarray, proteomic, and other omics). While the first portion of the book contains chapters discussing pediatric cancer, the influence of environmental factors and oncogene activity in tumorigenesis, the second portion of the book is structured by organ sites (Esophagus, Breast, Pancreas, Colon, Lung, Prostate, Skin, Brain, Endocrine System, Lymphoid System, Bone, Head and Neck, and Cervix). This format provides the reader with easy access to the needed information. This definitive text will offer the medical professionals, whether in research, academia or clinical practice, the latest information endorsed by the world renowned contributors. The broad range of topics will make this a valued reference and provide a wealth of information, making this a "state of the science" on carcinogenesis.